Antimicrobial activities of metal-natural extract complexes - How, Fiona Ni Foong; Kaida, Siti Aminah; Darnis, Deny Susanti; Arief Ichwan, Solachuddin Jauhari (2017)
Pluchea indica (L.) less, Clinacanthus nutans and Phyllanthus niruri are traditional herbs that possess some biological properties. This research is carried out to synthesize metal-natural extract complexes of Pluchea indica (L.) less, Clinacanthus nutans and Phyllanthus niruri and to study the antimicrobial of the metal-natural extract complexes. Leaves of Pluchea indica (L.) less, Clinacanthus nutans and Phyllanthus niruri were collected and extracted with methanol and ethanol and synthesized with various transition metal salts to yield metal-natural extract complexes. The metal-natural extract complexes were assessed for the antimicrobial activity using the disc diffusion method and determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values against four pathogenic bacteria which are Staphylococcus aureus (ATCC 29213), Bacillus cereus (ATCC 117788), Pseudomonas aeruginosa (ATCC 27853) and Escherichia coli (ATCC 25922). Investigation of antimicrobial activities of the complexes against the tested microorganisms showed that the metal-natural extract complexes were found to be more active against the organisms than the crude extracts itself. This study shows the potential of metal-natural extract complexes of Pluchea indica (L.) less, Clinacanthus nutans and Phyllanthus niruri as source of antimicrobial agents that will give contribution to the field of medical and pharmaceutical.